1981
DOI: 10.1210/jcem-52-5-924
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Histamine and H1and H2Receptors on Prolactin and Luteinizing Hormone Release in Humans: Sex Differences and the Role of Stress

Abstract: The present experiments were performed to investigate the possible role of histamine and its receptors, H1 and H2, in the control of PRL and LH release in normal adult humans of both sexes. Histamine infusion (200 microgram, iv, in 15 min) induced PRL and LH release in men; in women, histamine inhibited LH release without affecting PRL release. Two H1 antagonists, dexchlorpheniramine (10 mg, iv) and promethazine (50 mg, im), reduced PRL release in both sexes, stimulated LH release in men, and inhibited LH rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…In contrast a recent study in normal human males [17] showed a significant stimulation of the basal LH secre tion by an even lower dose of HA. This discrepancy is not readily explainable.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In contrast a recent study in normal human males [17] showed a significant stimulation of the basal LH secre tion by an even lower dose of HA. This discrepancy is not readily explainable.…”
Section: Discussioncontrasting
confidence: 76%
“…In ovariectomized estrogen/progesterone primed rats and in proestrus rats HA administered intraventricular ly stimulated LH secretion [5,13]. No effect of HA was found in estrus and diestrus rats [5],In humans, HA administered as an intravenous infusion was found to stimulate basal LH secretion in males and to inhibit basal LH secretion in females in the early follicular phase [17]. Intravenous injections of the H2-receptor anta gonists cimetidine (C) and ranitidine did not affect the go nadotrophin secretion [3,10], Long-term treatment with cimetidine has been found to increase basal as well as LRHstimulated gonadotrophin secretion [10,16,23], However, this stimulation is presumably caused by an anti-androgen effect of cimetidine rather than by a blockade of ^-recep tors [10,26].…”
mentioning
confidence: 97%
“…It ap pears, therefore, that histamine might involve activation of H2-receptors to increase the release of prolactin. However, this view contrasts with a dual role of histamine postulated on the basis of results obtained with histamine agonists and antagonists which indicated inhibition through H2-receptors and stimulation of prolactin release through Hi-receptors [1,26]. Since the specificity of the histaminergic agents was not examined in the above-mentioned studies, it can be concluded that the identity of receptors mediating the his tamine effect on prolactin release remains unproven.…”
mentioning
confidence: 93%
“…Our current understanding of the role of histamine in the regulation of LH release in humans is restricted to a series of studies that predominantly involved H2 antagonists administered peripherally (48 -55); no H2 receptor-specific effects on circulating levels of LH have been demonstrated. In contrast, the reported effects of H1 antagonists include the suppression of LH in women and its elevation in men (50); paradoxically, comparable sex-dependent effects were achieved with peripherally administered histamine (50). Nevertheless, the H1 antagonist employed in another study (49) was without effect on LH levels in either sex.…”
Section: Discussionmentioning
confidence: 94%